Facilely prepared nickel‑manganese layered double hydroxide-supported manganese dioxide on nickel foam for aqueous asymmetric supercapacitors with high performance. (15th August 2023) - Emin, Adil; Li, Junshuai; Dong, Yunxia; Fu, Yujun; He, Deyan; Li, Yali
Abstract: In order to achieve high-performance and long-lifespan supercapacitors, highly electrochemically active materials and rational structural design of are highly desirable. Herein, a hierarchical electrode structure of nickel (Ni)‑manganese (Mn) layered double hydroxide (NiMn-LDH)-supported manganese dioxide (MnO2 ), i.e., NiMn-LDH@MnO2, assembled by NiMn-LDH nanoparticles and MnO2 nanosheets was developed on nickel foam by facile electrodeposition and the subsequent hydrothermal reaction. The optimized NiMn-LDH@MnO2 electrode shows a high capacitance (~ 4336.8 F g −1 at 1.0 A g −1 ), good rate performance (~ 860 F g −1 at 60 A g −1 ) and long cycle stability (~ 83.2 % initial capacitance retention after 10, 000 cycles at 20 A g −1 ). Furthermore, the aqueous asymmetric supercapacitors using the optimized NiMn-LDH@MnO2 cathode and activated carbon anode demonstrate a desirable energy density of ~104.51 W h kg −1 at 800.00 W kg −1, and good cycle stability with 86.8 % initial capacitance retention and about 100 % Coulomb efficiency after 22, 000 cycles at 5.0 A g −1 . The above results indicate that this study offers a meaningful exploration for manufacturing the energy storage devices with high comprehensive performance. Graphical abstract: An aqueous asymmetric supercapacitor with the energy density of ~104.51 W h kg −1 at 800.00 W kg −1 is reported based on the NiMn-LDH@MnO2 heterostructure cathode facilely prepared by electrodeposition and the subsequent hydrothermal process. Unlabelled Image Highlights: A capacitance of 4336.8 F g −1 at 1.0 A g −1 was obtained for NiMn-LDH@MnO2 . An energy density of 104.51 W h kg −1 at 800.00 W kg −1 was achieved for the aqueous supercapacitors. The supercapacitors exhibit high stability even up to 22, 000 cycles.